Experimental and Analytical Investigations on Tribological Properties of PTFE/AP Composites - Wang, Hai; Sun, Annan; Qi, Xiaowen; Dong, Roger; Fan, Bingli (MDPI AG, 2021)
The tribological properties of polytetrafluoroethylene (PTFE)/AP (poly(para-phenyleneterephthalamide) (PPTA) pulp) composites under different test conditions (load: 2N,10N; frequency: 1 Hz, 4 Hz; amplitude: 2 mm, 8 mm) were holistically evaluated. PTFE/AP composites with different AP mass ratios of 3%, 6%, and 12% as a skeleton support material were prepared. The coefficient of friction (COF) and wear rate were determined on a ball-on-disk tribometer. Furthermore, the morphology, element composition, and chemical structure of the transfer membrane were analyzed accordingly. The relationships between load, frequency, amplitude, and tribological properties were further investigated. According to the wear mechanism, AP enables effective improvement in the stiffness and wear resistance, which is also conducive to the formation of transfer films.